Hematologic Challenges in the Critically Ill (Springer International Publishing, 2018)
This volume provides a comprehensive overview of hematologic issues that clinicians regularly encounter in the critical care environment. The text features hematologic scenarios that affect the adult ICU patient, outlines pathogenesis and challenges associated with the hematologic disorder, and offers treatment modalities. Hematologic issues covered include anemia, hemostatic abnormalities, and risks of transfusion. The book also details challenges in specific ICU populations, such as patients afflicted with liver disease, brain injury, sepsis, cardiovascular disease, malignancy, and trauma. Written by experts in the field, Hematologic Challenges in the Critically Ill is a valuable resource for clinicians in the critical care environment who treat critically ill patients afflicted with hematologic complications.